Catheter‐Related Bloodstream Infections Among Hemodialysis Patients in Northern Tanzania: Insights From a Single‐Centre Retrospective Study - Andrea R. Costantine; Sarah J. Urasa; Abid M. Sadiq; Elichilia R. Shao; Furaha S. Lyamuya; Elieishiupendo M. Niccodem; Eugénie M. Kamabu; Venance P. Maro; Elifuraha W. Mkwizu; Nyasatu G. Chamba; Francis F. Furia; Tumaini E. Mirai; et al. (Health Science Reports)
ABSTRACT Background and Aims A catheter‐related bloodstream infection (CRBSI) is a life‐threatening complication of hemodialysis. It is responsible for significant morbidity and mortality and a costly long hospital stay. Despite its burden, little is known about the factors associated with it and the antibiogram of its responsible causative bacteria. This study aimed to evaluate the determinants of hemodialysis CRBSI and the appropriate antibiogram for the isolated bacterial pathogens among patients attending the KCMC hemodialysis unit. Methods A hospital‐based retrospective analytical cross‐sectional study involved adult patients with CKD or AKI undergoing hemodialysis at KCMC with tunneled or non‐tunneled central venous catheters who attended from January 1, 2021 to December 31, 2022. Data were collected from the hospital's electronic medical record system. Statistical analysis was performed using SPSS version 27. Multivariate logistic regression was used to determine the factors associated with CRBSI. A p‐value of < 0.05 was considered statistically significant. Results A total of 286 patients were analyzed. The patients were predominantly males (70.6%), and more than half were above 55 years old (56%), with a mean age of 58 (SD ± 14.8) years. 56.6% developed CRBSI and were predominantly gram‐positive (69.7%). Major associated factors were hypoalbuminemia of < 35 g/dL, diabetes mellitus, anemia of hemoglobin < 10 g/dL, and having a femoral central venous catheter. For gram‐positive bacteria, the most efficient antibiotic was vancomycin, with an overall average efficacy of 99% for all isolates. For gram‐negative bacteria, the most efficient antibiotic was meropenem, with an overall average efficacy of 82.1% for all isolates. Conclusion Over 50% of patients developed CRBSI and gram‐positive bacteria were the major causative bacteria. Associated factors were multifactorial and preventive care would be ideal to reduce the number of CRBSI based on these findings.